Characterizing the Pattern of Anomalies in Congenital Zika Syndrome for Pediatric Clinicians - Moore, Cynthia A; Staples, J Erin; Dobyns, William B; Pessoa, André; Ventura, Camila V; Fonseca, Eduardo Borges da; Ribeiro, Erlane Marques; Ventura, Liana O; Neto, Norberto Nogueira; Arena, J Fernando; Rasmussen, Sonja A (JAMA pediatrics, 2017)
Zika virus infection can be prenatally passed from a pregnant woman to her fetus. There is sufficient evidence to conclude that intrauterine Zika virus infection is a cause of microcephaly and serious brain anomalies, but the full spectrum of anomalies has not been delineated. To inform pediatric clinicians who may be called on to evaluate and treat affected infants and children, we review the most recent evidence to better characterize congenital Zika syndrome. We reviewed published reports of congenital anomalies occurring in fetuses or infants with presumed or laboratory-confirmed intrauterine Zika virus infection. We conducted a comprehensive search of the English literature using Medline and EMBASE for Zika from inception through September 30, 2016. Congenital anomalies were considered in the context of the presumed pathogenetic mechanism related to the neurotropic properties of the virus. We conclude that congenital Zika syndrome is a recognizable pattern of structural anomalies and functional disabilities secondary to central and, perhaps, peripheral nervous system damage. Although many of the components of this syndrome, such as cognitive, sensory, and motor disabilities, are shared by other congenital infections, there are 5 features that are rarely seen with other congenital infections or are unique to congenital Zika virus infection: (1) severe microcephaly with partially collapsed skull; (2) thin cerebral cortices with subcortical calcifications; (3) macular scarring and focal pigmentary retinal mottling; (4) congenital contractures; and (5) marked early hypertonia and symptoms of extrapyramidal involvement. Although the full spectrum of adverse reproductive outcomes caused by Zika virus infection is not yet determined, a distinctive phenotype-the congenital Zika syndrome-has emerged. Recognition of this phenotype by clinicians for infants and children can help ensure appropriate etiologic evaluation and comprehensive clinical investigation to define the range of anomalies in an affected infant as well as determine essential follow-up and ongoing care.